Political Movements and Electoral Behavior in Bangkok: An Analysis of Thailand’s 2023 General Election - Pongsawat, Pitch (King Prajadhipok’s Institute Journal, 2025)
This article presents the main findings of the research titled “Political Movements and Electoral Behavior in Bangkok: An Analysis of Thailand’s 2023 General Election,” commissioned by the King Prajadhipok Institute. The research has four objectives: 1) to collect and analyze data on the political movements and electoral behavior of political parties and candidates involved in the 2023 general election in the Bangkok area; 2) to collect and analyze data on voters’ political participation, expression, and engagement across various channels, as well as the political behaviors influencing their electoral decisions; 3) to collect and analyze data on the roles of other political actors involved in the 2023 general election in Bangkok, such as the Election Commission of Thailand, non-governmental organizations, civil society, and the media; 4) to study the patterns and influences of online media on electoral behavior and election outcomes. The research was conducted using a combination of documentary research, statistical data collection and analysis, and interviews with various stakeholders, including party representatives, candidates, media personnel, officials from the Election Commission of Thailand, canvassers, and experts. The study yielded four main findings: 1. There was a change in the political movement and behavior of political parties and candidates in the 2023 Bangkok general election compared to the previous 2019 election. A voting system similar to the two-ballot system established by the 1997 constitution was reintroduced, and the voting constituency map for Bangkok was redrawn from 33 to 30 units. Additionally, the political dynamism since the 2019 election contributed to changes in the political movement and behavior of political parties and candidates in the 2023 Bangkok general election. Specifically, the changes in political movement and behavior were influenced by several factors: the second administration of General Prayut Chan-o-cha, which derived its legitimacy from the Palang Pracharat Party’s electoral victory in the 2019 general election; the dissolution of the popular Future Forward Party; the impact of the COVID-19 pandemic; the rise of youth political movements; and the landslide victory of Chatchart Sittiphan, who ran as an independent candidate in the 2022 Bangkok governor election. In the 2023 general election in Bangkok, the Move Forward Party, which was established following the dissolution of the Future Forward Party in 2020, achieved a landslide victory in both the Party List and popular votes. For the constituency vote, the Move Forward Party won 32 seats, while the Pheu Thai Party secured 1 seat. The Palang Pracharat Party, the winner of the 2019 Bangkok general election, received no seats in Bangkok. 2. There is a 73.90% turnout rate for the 2023 general election in Bangkok, compared to a 72.51% turnout rate in 2019. This increase signifies the rising political awareness of Bangkok’s population in connection with the popularity of the so-called “natural online canvassers.” Moreover, this rising political awareness of Bangkok’s population has also arisen from an increase in political conflict since 2019, as the party that formed the government coalition after the previous election did not win the majority of votes in Bangkok. The results of the 2023 general election in Bangkok reveal a drastic decline in the vote share of all the parties that were part of the incumbent government. 3. Other actors who played significant roles in the 2023 general election in Bangkok include the Bangkok field office of the Election Commission of Thailand, civil society, and the media. The Bangkok field office of the Election Commission regulated and managed the election. Civil society and the media increasingly took on roles in reporting, monitoring, and hosting both online and offline debates. The role of traditional local canvassers in the community has declined due to changes in urban life in Bangkok and the growing presence of online social media. 4. Mainstream and online media played a significant role during the election. The main differences between the previous Bangkok national election in 2019 and the 2022 election are people’s interest in online and offline debates, as well as the popularity of TikTok during election campaigns. The Move Forward Party skillfully utilized and benefited from this new online community and technology. TikTok has a unique algorithm that differs from those of other social media platforms. This algorithm allows different ideas to cross the walls of echo chambers more easily. This ease of crossing the echo chamber walls led to the emergence of a new group of organic online canvassers who could share a larger volume of campaign messages compared to older forms of social media, such as Facebook and Line.